Appendiceal neoplasms: evaluation of 4761 appendectomy specimens - Kemal Eyvaz; Mehmet Olcum; Murat Kazım Kazan; Kadir Balaban; Arif Aslaner; Tugrul Cakir; Nedim Akgul (Medicine Science, 2022)
Acute appendicitis is the most diagnosed intraabdominal pathology in emergency surgery meanwhile appendiceal neoplasms are infrequent and mostly detected in postoperative pathological work-up. In this study, we aimed to identify the incidence of appendiceal neoplasms and histopathological distribution of appendectomy specimens of our patients operated with the diagnosis of acute appendicitis. Between January 2010 and December 2020 postoperative results of patients who were operated with the diagnosis of acute appendicitis in a tertiary hospital were evaluated. Appendiceal neoplasms and subtypes of neoplasms according to pathology specimens are noted and long-term results of patients diagnosed with malignancy are given. 4761 patients operated for acute appendicitis while 55 (1.1%) of them had neoplasms on postoperative pathological evaluation. Eighteen out of 55 patients (32.7%) there were neuroendocrine tumor and in 36 patients there were mucinous lesions with different grades. Low-grade appendiceal mucinous neoplasms were the most common mucinous lesions. No statistically difference in terms of age and sex between group1 (patients who had appendicitis) and group 2 (patients who had neoplasm). Acute appendicitis is an emergent situation where the routine histopathological examination of specimens should be carefully performed to rule out malignancy. [Med-Science 2022; 11(1.000): 116-9]